AVALIAÇÃO DA RESISTÊNCIA DE UNIÃO, NANOINFILTRAÇÃO E CARACTERÍSTICAS MORFOLÓGICAS DA ZONA HÍBRIDA FORMADA POR DIFERENTES SISTEMAS ADESIVOS EM DENTINA EROSIONADA PREVIAMENTE TRATADA COM PASTAS DESSENSIBILIZANTES - Cardenas, Andrés Felipe Millán (2014)
This " in vitro " study evaluated the effect of the treatment of eroded dentin with bioglass (Novamin®) and casein phosphopeptides and amorphous calcium phosphate (CPP-ACP) in bond strength, nanoleakage and micromorphology of the hybrid layer, using three different adhesive systems. The sample consisted of 60 extracte human molars. The occlusal surfaces of the teeth were exposed at medial dentin, the smear layer were standardized and the induction of the dentin erosion were accomplished before restoration. The molars were randomly divided into 3 groups (n=20) according to the adhesive system used:G1 - Single Bond 2 ™ / 3M - ESPE ™ system, simplified 2 steps adhesive; G2 - AdheSE Ivoclar/Vivadent, 2 steps self- etch adhesive system and G3 -Universal Single Bond™ /3M-ESPE™, 1-step adhesive system. Previously to application of the adhesive system, each group was divided into 4 subgroups (n=5), according to the treatment which the dentin was submitted: S1 – Sound dentin (control), S2 - eroded dentin, S3 - eroded dentine + toothpaste with fluorine and bioglass and S4 - eroded dentine + toothpaste with CPP-ACP. After the application of the adhesive systems according to manufacturer's specifications, the teeth were restored with composite resin and sectioned to obtain "sticks-like" (specimens 0.8 mm2). The microtensile bond strength test (TBS) was performed after 24h of storage in water at 37 ºC at a rate of 1mm/min. Before the microtensile test, 4 “sticks-like” for each experimental conditions were randomly assigned for the analysis of the hybrid layer, resin tags and nanoleakage (NI) by SEM. The TBS and NI data were analyzed by 2 away-ANOVA complementary Tukey's test (α=0.05). The Adper Single Bond 2 system after pretreatment with fluorine-based and bioglass and CPP-ACP showed the highest TBS means (53.39 ± 7.88 MPa and 47.72 ± 10.68 MPa, respectively). The lowest TBS mean was observed for the self etch adhesive system (AdheSE) after erosion (14.04 ± 7.28 MPa). The higher NI mean (%)was observed for AdheSE + eroded dentin (69.40 ± 8.73) and Single Bond 2 had the lowest NI mean (%) for treatment with fluoride and bioglass and CPPACP (11.16 ± 1.34 and 15.63 ± 1.47, respectively). The morphological analysis of the micrographs from the subgroups S3 and S4 for adhesives Single Bond 2 and Single Bond Universal showed the presence of more homogeneous resin tags compared to the other tested conditions. The best nanoleakage condition were obtained for Single Bond 2 and Single Bond Universal system. It was concluded that the home or professional application of desensitizing pastes does not interfere with the TBS in eroded dentin, maintaining or improving the TBS for this substrate.